2016
DOI: 10.1111/aos.13000
|View full text |Cite
|
Sign up to set email alerts
|

Epidemiology and aetiology of childhood ocular trauma in the Republic of Suriname

Abstract: ABSTRACT.Purpose: To describe the epidemiology and aetiology of ocular trauma in schoolaged children who previously visited the Suriname Eye Centre (SEC) of the Academic Hospital Paramaribo. Methods: In a hospital-based retrospective study, all cases of children who were school aged (8-15 years) at the time of the survey and previously underwent evaluation and/or treatment at the SEC because of ocular trauma were analysed. Demographic and ophthalmologic data were taken out of patient records; eye injuries were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 19 publications
5
8
0
Order By: Relevance
“…In contrast with our results, a study conducted in Lithuania by Puodžiuvienė et al [14] found that CGI was the most common type of eye injury in children. Similar results were also presented in other studies [15][16][17].…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In contrast with our results, a study conducted in Lithuania by Puodžiuvienė et al [14] found that CGI was the most common type of eye injury in children. Similar results were also presented in other studies [15][16][17].…”
Section: Discussionsupporting
confidence: 92%
“…A low education level, lack of safety awareness and lack of protective eyewear may lead to the occurrence of eye injury. Additionally, we found that male children were more likely to be injured than female children, consistent with data from other studies [16,22,23].…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Importantly, ophthalmic trauma is the leading cause of unilateral non-congenital blindness in children, representing significant impact on quality of life and productivity. 6,12,13,18,19 Ophthalmic trauma cases with minor plaintiffs were more likely to be resolved in favor of the plaintiffs (53.3% vs 37.9%; P=0.35) and to have higher jury awards ($687 454 vs $572 451; P=0.64) than cases with adult plaintiffs, but neither were found to be of statistical significance. We have previously reported a similar trend in ophthalmology, in which cases with pediatric plaintiffs are more likely to have plaintiff verdicts and were associated with higher monetary awards.…”
Section: Discussionmentioning
confidence: 88%
“…Ocular trauma is the main cause of damage to children's vision [1,2], which not only severely affects children's visual development and physical and mental health, but also causes great loss to family and society. The incidence rate of paediatric ocular trauma in developing countries accounts for 1 in 1000 [3,4].…”
Section: Introductionmentioning
confidence: 99%